Study on the Application of OTN Based IP Offloading Technologies - Ruiquan Jing (Dianxin kexue)
The basic concept of OTN-based IP offloading was introduced, then the characteristics and advantages of IP offloading were analyzed. The key technologies related to the IP offloading were also discussed, including internetworking interface, connection establishment mode and OAM. Additionally, the economics of OTN-based IP offloading was analyzed.